APLIKASI MOBILE LEARNING BERBASIS ANDROID - Wibowo, Eric Adie; Arifudin, Riza (Unnes Journal of Mathematics, 2016)
The purpose of this article is to design and implement mobile learning applications based on Android at SMAN 5 Semarang. Applications developed using prototype method, the process of software development activities include the design needs analysis, implementation, and testing. Applications created with features that include viewing the content, news, download materials, assignments, and grades. Testing was conducted using Blackbox test and testing by the user. The final results reveal that the application can be implemented properly in android device with type mobile phones and tablets that have a version of 2.3 Gingerbread to 4.3 Jelly Bean with a variety of screen sizes